A Theoretical Incinerator Design for Treatment of Biomedical Wastes Generated from Local Hospitals in Baghdad - Ahmed H. Hadi; Basim A. Hussain; Mais J. Mohammed; Wasnaa J. Mohammed; Abdullah F. Abdurazak (Journal of Engineering)
A theoretical study is done to treat Baghdad biomedical wastes (5.21 tons/day) using many treatment methods according to construction and maintenance costs, energy and water consumption and decreasing waste volume and mass. Previous published experimental data results and experimental operation conditions are considered in the current research. The thermal energy and generated wastes are computed from the complete combustion of biomedical wastes (100 kg/h) from two hospitals in Baghdad. Survey data shows that the Medical City and Al-Yarmouk Hospital generate about (700 kg /day) of biomedical waste. A multi-chamber incinerator with a capacity of (100 kg/h) has been designed to burn biomedical wastes using diesel fuel to reach (1100˚C) as a burning temperature. The resulting thermal energy was computed to be (0.7178565 MW) which is emitted directly with flue gases to the ambient without any off-gas system. The mass of flue gases is found to be (1895.8175 kg/h) and the gases are (193.20872 kg/h for CO2 and 1.6352 kg/h for HCl) through using excess air ratios at 150% for solid wastes burning and 20% for liquid fuel burning. The required cement and water are determined for resulting ash to produce concrete suitable for hot weather countries. The results show that incineration has the less costs in construction and operational costs among other modern technologies with a decreasing waste mass to 91.5%.